Development of a Personal-Social Guidance Program to Enhance Student Discipline - Erni Astini; Saryanto Saryanto; Rahmat Mulyono (CV Edujavare Publishing, 2026)
At the elementary school level, discipline is understood not only as adherence to rules but also as the process of internalizing positive values that will influence students' future academic, social, and emotional development. This study aims to develop a social personal guidance program to improve the discipline of elementary school students at SD Negeri 3 Kalikajar. The study used a Research and Development (R&D) approach with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The results of the study indicate that the condition of student discipline still needs to be improved, especially in aspects of punctuality, compliance with rules, responsibility in completing assignments, and orderly learning. The social personal guidance program developed was compiled based on an analysis of student needs and validated by experts so that it was declared feasible to be implemented in elementary schools. The implementation of the program through classical services, group guidance, habituation, and positive reinforcement showed a change in student discipline behavior towards the better. Thus, the social personal guidance program is effective as a systematic effort to improve the discipline of elementary school students through a preventive, developmental, and needs-based approach.